Ischemic duration determines extent of cardiac remodeling, and both early and delayed reperfusion prevent fatal cardiac rupture: Model comparison - Ling Zhao; Amanguli Ruze; Guo-Li Du; Min-Tao Gai; Jing Tang; Xiao-Ming Gao (PLoS ONE, 2025)
High incidence of cardiac rupture in murine myocardial infarction (MI) model leads to a substantial loss before the study end-point. Selecting animal models with varying degrees of injury for different research purposes is crucial for cardiovascular research. Male C57 mice were subjected to ischemia/reperfusion (I/R) or permanent occlusion (MI) injury. The incidence of cardiac rupture, degree of myocardial injury, inflammatory responses, left ventricular (LV) remodeling and infarct myocardium healing were examined. Compared to MI mice, early reperfusion (1, 2 and 4h I/R) completely prevented cardiac rupture, while delayed reperfusion (12h and 24h I/R) significantly reduced incidence of cardiac rupture to 5.7% and 8.6%, respectively. In the acute phase, prolonged ischemia increased infarct size, myocyte apoptosis, and both systemic and regional inflammatory responses. These changes correspond to enhanced MMP-9 activity and a weakening of the tensile strength of the infarcted myocardium. Following ischemic insult, early reperfusion was associated with less extent of myocardial injury, inflammatory response and adverse cardiac remodeling, whereas, delayed reperfusion and MI groups exhibited severe myocardial damage and remodeling. Furthermore, both early and delayed reperfusion were associated with increased infiltration of type 2 macrophages and proliferation of endothelial cells during the early healing phase, thereby facilitating healing of the infarct myocardium. Delayed reperfusion resulted in a comparable and substantial degree of cardiac remodeling but with a lower risk of cardiac rupture in comparison with MI model. This feature makes it a feasible model for cardiac ischemia research.